2001
DOI: 10.1046/j.1365-2869.2001.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Daytime variations in central nervous system activation measured by a pupillographic sleepiness test

Abstract: Pupil size is regulated exclusively by the autonomic nervous system, and in darkness is proportional to the level of central sympathetic tone. Spontaneous pupillary movements, while at rest in darkness and quiet, were recorded for a period of 11 min, using infrared video pupillography. Thirteen young adults took part in a 30‐h experiment lasting from 08.00 h to 14.00 h on the following day. Pupillographic testing and completion of a self‐rated scale for the estimate of sleepiness were repeated every two hours.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 18 publications
12
112
1
7
Order By: Relevance
“…There was a main effect of block, F(4, 140) = 3.75, MSE = .04, p < .01, partial η 2 = .10, and a significant linear trend, F(1, 35) = 9.30, MSE = .01, p < .01, partial η 2 = .21. Overall, the decrease in pupil diameter and the increase in pupil variability are consistent with increases in pupillary unrest as time on task increases, suggesting that as time on task increased participants alertness and arousal decreased (Morad et al, 2000;Wilhelm et al, 2001).…”
Section: Pupil Diametersupporting
confidence: 52%
“…There was a main effect of block, F(4, 140) = 3.75, MSE = .04, p < .01, partial η 2 = .10, and a significant linear trend, F(1, 35) = 9.30, MSE = .01, p < .01, partial η 2 = .21. Overall, the decrease in pupil diameter and the increase in pupil variability are consistent with increases in pupillary unrest as time on task increases, suggesting that as time on task increased participants alertness and arousal decreased (Morad et al, 2000;Wilhelm et al, 2001).…”
Section: Pupil Diametersupporting
confidence: 52%
“…It has been argued that pupillary fatigue oscillations are a result of decreases in sympathetic nervous system (SNS) activation of the Edinger Westphal nuclei and decreases in the parasympathetic nervous system (PSNS) inhibition of the Edinger Westphal nuclei [13]. Since both systems are part of the peripheral nervous system (PNS), it is possible that gum chewing is only affecting PNS changes in arousal and not the central nervous system (CNS).…”
Section: ])mentioning
confidence: 99%
“…For example, mint flavour has been associated with increased alertness. Norrish and Dwyer [12] employed the Pupillograpy Sleepiness Test (PST) and demonstrated that exposure to a peppermint odour can attenuate pupillary unrest (an inverse correlate of self-rated alertness [13]). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations